Family as a space for biographical learning - Kuryś-Szyncel, Karolina (Biografie rodzinne i uczenie się: Tom 8, 2021)
The paper assumes that family as a system is also a space for biographical learning. Introduced the author’s category „family biography” as multiply (which is more than the sum of unit biographies), subject to the systematic rules of circulation and equipotential infinite reconstruction resulting from the tensions between the course of family life and the story of life history. Transmission of patterns in such a family system is accomplished through the sharing of meanings during close biographical inter- and intra-generational meetings, which the author proposes to call Joint Biographical Involvement Episodes. The implications for pedagogical family therapy were also indicated.